2002
DOI: 10.1016/s1388-9842(02)00091-0
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous angiotensin converting enzyme inhibition moderates ventricular dysfunction caused by doxorubicin

Abstract: Aims: The purpose of this study was to determine that the administration of an angiotensin converting enzyme (ACE) inhibitor enalapril would confer protection against doxorubicin-induced experimental heart failure, and attenuate the development of left ventricular dysfunction. Methods: Seventeen dogs were chronically instrumented with an intracoronary catheter and received doxorubicin weekly for 4 weeks. Animals were assigned to two groups: group 1: untreated heart failure; and group 2: simultaneous enalapril … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(35 citation statements)
references
References 17 publications
(14 reference statements)
0
34
0
1
Order By: Relevance
“…16 Then again, an increased oxidative stress has been indicated as a possible primary mechanism in the development of anthracycline- induced cardiac toxicity. In several studies, both sulfydryland non-sulfydryl-containing ACEIs have been shown to be effective free radical scavengers, having an antioxidant effect on adriamycin-induced cardiotoxicity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…16 Then again, an increased oxidative stress has been indicated as a possible primary mechanism in the development of anthracycline- induced cardiac toxicity. In several studies, both sulfydryland non-sulfydryl-containing ACEIs have been shown to be effective free radical scavengers, having an antioxidant effect on adriamycin-induced cardiotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…9 -12 Furthermore, data referring to experimental models suggest that the cardiac renin-angiotensin system (RAS) plays an important role in the development of anthracycline-induced cardiomyopathy and that treatment with ACEIs protects against chemotherapy-induced cardiotoxicity. [13][14][15][16][17][18][19] Hence, it is likely that a prophylactic strategy based on the use of ACEIs in selected high-risk patients could prevent cardiotoxicity.…”
Section: Editorial P 2432 Clinical Perspective P 2481mentioning
confidence: 99%
“…A number of pharmacologic trials investigating common cardiovascular drugs as well has been investigated to reduce cardiac toxicity of doxorubicin. Both antiadrenergic therapy using h-blockers and inhibition of the renin-angiotensin system can reduce the progression of this disease at the early stage of cardiotoxicity (21)(22)(23). Regarding these drugs, anti-inflammatory effects and changes in LV loading conditions contributed to their ability to attenuate cardiac damage after doxorubicin treatment.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in addition to their vasodilatory effects, ACEI and exercise training are also potent antioxidants and actively scavenge ROS and lower oxidative stress (48). Because radiotherapy and certain cancer chemotherapeutics rely on ROS-mediated deoxyribonucleic acid damage to induce apoptosis, one could speculate that these interventions might inhibit the efficacy of these therapies.…”
Section: Breast Cancer and Cardiovascular Injury: Prevention And/or Tmentioning
confidence: 99%